Determination of an engineering model for exchange kinetics of strong acid cation resin for the ion exchange of sodium chloride & sodium bicarbonate solutions. (June 2017) - Millar, Graeme J.; Miller, Gavin L.; Couperthwaite, Sara J.; Dalzell, Scott; Macfarlane, David
Highlights: The BWS kinetic expression was found to be an optimal engineering model for sodium exchange with SAC resin. Anion identity influenced cation exchange kinetics with SAC resins. Sodium ion exchange rates depended upon resin/liquid ratio. Rate limiting step in exchange kinetics changed with time and resin/liquid ratio. Abstract: This study identified an appropriate engineering model which described the exchange kinetics of sodium ions with a strong acid cation resin. Synthetic resins have potential application for the demineralization of coal seam (CS) water prior to beneficial reuse. However, there is limited data regarding the kinetic behaviour of strong acid cation (SAC) resin for the removal of sodium ions, the most prevalent ions in the water collected from coal seams (produced water) during natural gas extraction. In particular, exchange kinetics need to be understood in relation to estimating how full scale columns of resin may perform. Kinetic analysis revealed that the exchange of sodium ions from both sodium chloride and sodium bicarbonate solutions with SAC resin reached equilibrium within minutes at ambient temperature. Optimal simulation of the kinetic data for both chloride and bicarbonate containing solutions was achieved by application of the Brouers, Weron and Sotolongo (BWS) fractal equation; and this should be used as the basis for development of an engineering model. The model parameters varied depending upon the ratio of resin to liquid employed in the tests, with rates showing substantial enhancement once an excess of resin exchange sites were present. The exchange process was apparently controlled in part by intraparticle diffusion, with three phases inferred for sodium chloride solutions and two for sodium bicarbonate solutions. Other rate limiting phenomena such as film diffusion appeared to play a role under certain conditions.